Oral Hygiene Examination and Dental Health Education of Children at Islamic Boarding School Palembang - Martha Mozartha; Sri W. Rais; Siti Rusdiana Puspa Dewi; Danica Anastasia; Arya Prasetya Beumaputra; Hema Awalia (HM Publisher, 2015)
Previous studies have shown that the majority of children in Indonesia have poor oral hygiene. Children who attend boarding school are sometimes facing difficulties in accessing dental health providers. In this kind of situation, knowledge of oral health and how to do a proper dental cleaning is crucial and must be mastered not only by students but also their teachers who spend most time with them at the boarding school. This goal can be achieved by the collaboration of dental public health and the school and community members.